Routledge handbook of public criminologies - Henne, Kathryn E.; Shah, Rita (Routledge handbooks, 2020)
Foreword : The state of public criminology - progress and challenges -- Introduction: Public criminology reconsidered - an invitation -- Part I. The emergence of public criminologies. Everything still to play for : revisiting public criminologies : diverse perspectives on academia and policy -- Re-thinking public criminology : politics, paradoxes, and challenges -- Where is the public in public criminology? Towards a participatory public criminology -- The challenge of transformative justice : insurgent knowledge and public criminology -- Articulation of liberation criminologies and public criminologies : advancing a countersystem approach and decolonization pardigm -- Part II. Engaging publics. A revolution in prosecution : the campaign to end mass incarceration in Philadelphia -- Reflctions from an accidental public scholar -- Engaging the public : access to justice for those most vulnerable -- Public feminist criminologies : reflections on the activist-scholar in violence against women policy -- Liberating abortion pills in legally restricted settings : activism as public criminology -- Part III. Barriers and challenges. Strangers within : carving out a role for engaged scholarship in the university space -- The push and pull of going public : barriers and risks to mobilizing criminological knowledge -- Public criminology in China : neither public nor criminology -- A case for a public pacific criminology? -- The challenges of academics engaging in environmental justice activism -- Part IV. Critiques and critical reflections. You're a criminologist? What can you offer us? Interrogating criminological expertise in the context of white collar crime -- Our North is the South : lessons from researching police-community encounters in Sāo Paulo and Los Angeles -- Confronting politics of death in Papua -- Rethinking how the public counts in public criminology -- Does the public need criminology? -- Part V. Future trajectories. Starting the conversation in the classroom : pedagogy as public criminology -- You are on Indigenous Land : acknowledgment and action in criminology -- Time to think about patriarchy? Public criminology in an era of misogyny -- Value-responsible design and sexual violence interventions : engaging value-hypotheses in making the criminological imagination -- Abolitionism as a philosophy of hope : inside-outsiders and the reclaiming of democracy.